2018
DOI: 10.1111/iju.13556
|View full text |Cite
|
Sign up to set email alerts
|

Role of bone scan index in the prognosis and effects of therapy on prostate cancer with bone metastasis: Study design and rationale for the multicenter Prostatic Cancer Registry of Standard Hormonal and Chemotherapy Using Bone Scan Index (PROSTAT‐BSI) study

Abstract: The baseline characteristics of the Prostatic Cancer Registry of Standard Hormonal and Chemotherapy Using Bone Scan Index database have been established. This collaborative study can now proceed with clarifying the role of the bone scan index for patient management including treatment strategies and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…17 The levels of PSA during tumor regression in mHSPC might decrease in cancer cells due to inactivation of the PSA promoter by androgen deprivation, whereas they might not necessarily parallel the amount of bone metastasis in mCRPC. 14 Bone scintigraphy remains the first-line whole-body survey of metastasis, even after the advent of X-ray computed tomography and magnetic resonance imaging. Although hot spots have been counted in previous prostate cancer working group activities, 5,6 recent advances in quantitation using artificial intelligence have enhanced their diagnostic utility for initial diagnosis and follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The levels of PSA during tumor regression in mHSPC might decrease in cancer cells due to inactivation of the PSA promoter by androgen deprivation, whereas they might not necessarily parallel the amount of bone metastasis in mCRPC. 14 Bone scintigraphy remains the first-line whole-body survey of metastasis, even after the advent of X-ray computed tomography and magnetic resonance imaging. Although hot spots have been counted in previous prostate cancer working group activities, 5,6 recent advances in quantitation using artificial intelligence have enhanced their diagnostic utility for initial diagnosis and follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In this context, we started the PROSTAT-BSI study to evaluate standard hormonal therapy and chemotherapy incorporating BSI, and patients were recruited from 30 hospitals. 14 The present study summarizes the findings of a nationwide prognostic study of the role of bone metastatic markers in standard hormonal therapy for mHSPC and chemotherapy for mCRPC.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, our study just focused on the performance of the AI model on the diagnosis of absence or presence of bone metastasis to assist nuclear medicine physicians' interpretation. However, a series previous study demonstrated that the bone scan index (BSI) calculated by artificial neural networks is an effective biomarker for predicting the prognosis or survival of some malignant cancers [26][27][28][29] . Whether our AI model could be beneficial to the assessment of the prognosis or survival of some malignant cancers like BSI, it might require more concentration on lesion-based analysis.…”
Section: Discussionmentioning
confidence: 99%
“…3 Since that time, several different researchers have shown the usefulness of automated BSI as a novel imaging biomarker for predicting chemotherapy response and prognosis in castration-resistant PC patients with bone metastasis, as well as hormone-sensitive PC patients. 6 They have presented a clear study design and rationale for the use of the Prostatic Cancer Registry of Standard Hormonal and Chemotherapy Using Bone Scan Index, along with initial background information about the registered patients. However, few prospective multicenter studies have been carried out to evaluate BSI in PC patients with bone metastasis.…”
mentioning
confidence: 99%
“…For the present study, Nakajima et al established a database of PC cases with bone metastasis, termed Prostatic Cancer Registry of Standard Hormonal and Chemotherapy Using Bone Scan Index, in order to accurately evaluate the importance of BSI in a prospective manner. 6 They have presented a clear study design and rationale for the use of the Prostatic Cancer Registry of Standard Hormonal and Chemotherapy Using Bone Scan Index, along with initial background information about the registered patients. To the best of my knowledge, this project is the first such prospective and multicenter study based on data obtained from Japanese patients.…”
mentioning
confidence: 99%